Perancangan Sistem Ekstruder untuk 3D Printer Cokelat - Pambudi, Abim Adhanis; Bekti Wibowo, Setyawan; Setiawan, Widia; Danny, stephanus (Jurnal Rekayasa Mesin, 2024)
The chocolate 3D printer is one such development, designed to assist humans in creating objects using chocolate as the base material. Chocolate 3D printers can produce a wide range of creative objects according to user preferences. This research project began with the design of the extruder components to be used in the chocolate extrusion process of the 3D printer. The components utilized in this design include the barrel and nozzle, Nema 17 stepper motor, 150 W 24 V silicon heater, single screw, hopper, and bracket. The design process was tailored to meet the specific requirements and objectives of this research. Experimentation will be conducted on the extruder by introducing variations in its printing speed. The research results indicate that the extruder can perform the extrusion process effectively using the mentioned components. At a temperature of 40 degrees Celsius and a print speed of 100 mm/s, the chocolate melt consistently flows out.